Meningococcal Meningitis in Sub-Saharan Africa: A Review - (:unkn) unknown (My University, 2022)
The scourge of Meningococcal Meningitis in the Sub-Saharan African nations is well known. This review paper focuses on this very important topic and describes the symptoms, diagnoses, and available vaccines for the same. The review then focuses on the Meningitis Belt of Africa and elucidates on the introduction of MenAfriVac™ vaccine. The review ends with the success of this vaccine and the future of Meningococcal Meningitis in the context of overall global climate change.
Keywords: African Research